Implementasi Manusia Ideal dalam Perspektif Muhammad Iqbal - Elsa Padia; Danny Abrianto; Zulfi Imran (Al-Ulum: Jurnal Pendidikan Islam, 2022)
As a Sufi figure and philosophical poet who was born in Sialkot, India. Iqbal has carved his life in such a way that it is remembered by mankind. This study uses library research research methods to collect data using a qualitative approach with a descriptive type of research. The results of this study indicate that first, the notion of an ideal human being according to Iqbal, cannot be separated from khudi. Iqbal gives the image of an ideal human being as a person who is aware of his immortality, his ownership of God's attributes, and his ability to show action, not just reaction. Khudi is the center or foundation of all life. Second, the implementation of the ideal human in Iqbal's perspective is through three stages, namely, obedience to the Divine Law, complete self-control and Divine niabad (Divine Caliph).